2021
DOI: 10.35772/ghm.2020.01120
|View full text |Cite
|
Sign up to set email alerts
|

The advances in dealing with the safety of medicated drugs in pregnancy

Abstract: The Japan Drug Information Institute in Pregnancy (JDIIP) was established with the aims of providing information on drug safety to women who are worried about drug use during pregnancy and creating evidence through epidemiological studies based on counseling cases. Since being established, JDIIP has made many contributions to the wellness of mothers and children by promoting the proper use of drugs during pregnancy. A network consisting of Core hospitals in 47 prefectures plays an important role in providing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…In fact, the Japan Drug Information Institute in Pregnancy (JDIIP) reported that among 4821 patients for the counseling regarding drug safety during pregnancy between 2005 and 2016, carbocisteine was the most frequently consulted drug (605 patients). 6,7 Similarly, the JDIIP also reported that among 13 000 patients for counseling from 2005 to 2018 in Japan, counseling about general cold medicine accounted for the second largest part of the counseling all over Japan, in which many of those drugs included carbocisteine and ambroxol. 8 However, no epidemiological study to date has investigated whether oral administration of carbocisteine and ambroxol during pregnancy is associated with an elevated risk of major birth defects in infants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the Japan Drug Information Institute in Pregnancy (JDIIP) reported that among 4821 patients for the counseling regarding drug safety during pregnancy between 2005 and 2016, carbocisteine was the most frequently consulted drug (605 patients). 6,7 Similarly, the JDIIP also reported that among 13 000 patients for counseling from 2005 to 2018 in Japan, counseling about general cold medicine accounted for the second largest part of the counseling all over Japan, in which many of those drugs included carbocisteine and ambroxol. 8 However, no epidemiological study to date has investigated whether oral administration of carbocisteine and ambroxol during pregnancy is associated with an elevated risk of major birth defects in infants.…”
Section: Introductionmentioning
confidence: 99%
“…These drugs prescribed for cold relief, rhinitis, and nasal sinuses inflammation are also frequently taken by reproductive‐aged women during their implantation period or early pregnancy, and when they notice the pregnancy, they become highly anxious about the effect of these drugs on fetal organogenesis. In fact, the Japan Drug Information Institute in Pregnancy (JDIIP) reported that among 4821 patients for the counseling regarding drug safety during pregnancy between 2005 and 2016, carbocisteine was the most frequently consulted drug (605 patients) 6,7 . Similarly, the JDIIP also reported that among 13 000 patients for counseling from 2005 to 2018 in Japan, counseling about general cold medicine accounted for the second largest part of the counseling all over Japan, in which many of those drugs included carbocisteine and ambroxol 8…”
Section: Introductionmentioning
confidence: 99%
“…In response, the Japan Drug Information Institute in Pregnancy (JDIIP) 5,6 was established in October 2005 within the National Center for Child Health and Development as a Ministry of Health, Labour, and Welfare project. As of April 2023, 57 facilities in 47 prefectures (including the National Center for Child Health and Development) are using this network to establish a foundation for prompt consultation.…”
Section: Introductionmentioning
confidence: 99%